Study on the Deposition Characters of Linear Multi nozzle NFES to Direct write Aligned Nanofibers - WANG Zhifeng; CHEN Xindu; ZHANG Jiarong; LIN Yaru; PENG Weichao; LIN Zeqin; WANG Han (Journal of Harbin University of Science and Technology)
Nearfield electrospinning (NFES) directwriting of linear multinozzle is a highly efficient electrohydrodynamic technique for massvolume fabricating micronano structures. To control charged jets to deposit aligned nanofibers accurate and denser with multiphysical coupling during linear multinozzle NFES process was crucial concern. In order to study the influence of electrospinning parameters on deposition distance of aligned nanofibers during linear multinozzle NFES. With orthogonal experimental design, the influence and sensitivity of needle length, needle spacing and applied voltage on deposition distance is investigated. Moreover, the method of improving density of aligned nanofibers by rotating multinozzle setup is proposed and proved. This study can be greatly contributed to guide to directwrite micro/nano structures in highefficient and accurate way.